Analisis Peningkatan Kemampuan Membaca Pemahaman Melalui Metode Shared Reading - karmita mita; Ramlah; Atika Auduna; Nurul Adha Albar (Universitas Muhammadiyah Kolaka Utara, 2025)
This study aims to analyze the effectiveness of the shared reading method in improving reading comprehension skills among elementary school students. The research was conducted through a literature review of ten articles published in national journals between 2020 and 2025, focusing on the application of shared reading in reading instruction. The findings indicate that shared reading enhances students’ comprehension, reading interest, and oral language skills by providing interactive, collaborative, and enjoyable learning experiences. It also fosters independent reading habits and positively influences students’ motivation. However, challenges such as low motivation, limited access to reading materials, and reliance on conventional teaching methods remain. Therefore, it is recommended that teachers integrate shared reading regularly using creative media, schools provide adequate literacy facilities, and future researchers develop technology-based learning models combined with shared reading to expand its effectiveness